Translation techniques and acceptability of translation in sentences containing religious term in the bilingual book entitled Prophet Nuh AS - Listimariam, Elen; Kustanti, Dewi; Budiarti, Dian (Journal of Research on English and Language Learning (J-REaLL), 2025)
Translation plays a crucial role in facilitating communication among people who speak different languages. However, challenges arise in maintaining the acceptability or cultural relevance. Many previous studies have examined translation techniques and translation quality assessments, but few have specifically explored the acceptability of sentences containing religious terms in bilingual books. This research focuses on analyzing types of translation techniques and the translation acceptability in sentences containing religious terms in a bilingual book entitled Prophet Nuh AS. This research utilized translation quality assessment, focusing on the acceptability aspects. A qualitative descriptive method was employed in this research by using the documentation technique to collect the data. The findings show that there are 5 translation techniques used in the translation of sentences containing religious terms, which are established equivalent, modulation, literal translation, amplification, and reduction. The dominant technique is the literal translation technique, while the least is the reduction technique. In terms of translation quality assessment of the acceptability aspect, the calculation of the quality score shows that the translation is acceptable. This research has limitations, including its focus on a single book, which may not adequately represent the broader context of translation. Future research could extend the scope by examining multiple religious texts to gain deeper insights. The results of this study imply that it is important for translators to improve their skills in applying effective translation techniques, as well as pay attention to the acceptability of the readers.